KINERJA SAHAM PERUSAHAAN KEUANGAN DAN NON KEUANGAN BERDASARKAN SHORT-TERM UNDERPRICING DAN LONG-TERM UNDERPERFORMANCE - Andriani Pratiwi, I Gusti Ayu Made Agung Mas; Ramantha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this research is to investigate the difference in financial and non financial companies stocks performance that conducting an IPO at the Indonesia Stock Exchange in 2001-2011, based on the short-term underpricing and long-term underperformance. The sample was collected by using purposive sampling technique. The data analysis technique is different parametric test Independent Sample t-Test and different non parametric test Mann-Whitney U Test. The research results obtained in this study shows that there are differences infinancial and non financial companies stocks performance that conducting an IPO at the Indonesia Stock Exchange in 2001-2011, based on the short-term underpricing. However, on long-term underperformance, the results shows that there is no difference in their stocks performance.
Keywords: Stock Performance, Financial Companies, Non Financial Companies, Underpricing, Underperformance